(untitled) (International Journal of Automation and Smart Technology, 2011)
Taiwan was gifted with a beautiful natural environment; however, it comes with a cost on this very unique geographical location. Natural disasters such as typhoons, torrential rains, debris flows, and earthquakes frequently cause severe damage and losses. The Taiwanese government and public are trying hard to prevent these disasters and protect its people by all means including scientific research, making laws and improving processing efficiency of corresponding official units. The National Applied Research Laboratories (NARL) is one of those lead roles among the battle between Taiwan and the Mother Nature. NARL has conducted studies on disaster prevention and responses, and applied electronic, modeling, and automation data analysis techniques to assist the government in disaster prevention and rescue. These techniques have positively influenced disaster reduction and preparedness,